2017
DOI: 10.33407/itlt.v62i6.1937
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Education With Electronic Educational Game Resources in Primary School

Abstract: The article presents the results of a pedagogical experiment on the study of the effectiveness of education with electronic educational game resources (EEGR) in mathematics, conducted during the experimental work “Rozumnyky” (Smart kids). The obtained results, verified by the mathematical statistics, showed the positive effect of the use of EEGR when studying mathematics on the level of educational achievements, the development of memory and thinking of the experimental group pupils. During the experiment ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As noted in the work of V. Yu. Bykov and S. G. Lytvynova (Bykov, Lytvynova, & Melnyk, 2017), which reveals the results of an experiment on the use of electronic educational and game resources. During the study, researchers found positive changes in the development of learning motivation of those students who studied using electronic educational and game resources.…”
Section: Features Of Using the Discord Messenger In The Learning Processmentioning
confidence: 83%
“…As noted in the work of V. Yu. Bykov and S. G. Lytvynova (Bykov, Lytvynova, & Melnyk, 2017), which reveals the results of an experiment on the use of electronic educational and game resources. During the study, researchers found positive changes in the development of learning motivation of those students who studied using electronic educational and game resources.…”
Section: Features Of Using the Discord Messenger In The Learning Processmentioning
confidence: 83%
“…We consider it necessary to begin our analysis from defining educational digital games. Educational digital games or EduGames are also known as "video games for learning", "computer games", "applied games", "games for education", "learning games", "electronic educational game resource" (a term recently introduced by the Ukrainian scientific community) [6], "serious games", with the last term as a recent years' mainstream term that describes games for learning, training, healthcare and social change [28]. If video games are considered an activity that includes one or more players, has definite goals, rules, limitations, rewards and outcomes, is artificial with the element of a competition, then serious video games are those that are built on gamebased learning principles, include basic elements of video games and are used not only for the entertainment.…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of education with electronic educational game resources in mathematics, conducted during the study "Rozumnyky" (Smart kids) is described in the works of V. Bykov, S. Lytvynova and O. Melnyk [3]. They argue that using electronic educational game resources in the educational process showed a positive effect when studying mathematics (the level of educational achievements, the development of memory and thinking) [3].…”
Section: Of Computer Science Teachers' Readiness To Develop Computer mentioning
confidence: 99%